THE IMPACT OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. ZURICH INSURANCE IN TANGERANG - Hafis Laksmana Nuraldy; Imbron Imbron; Aldila Rahma Putri (Asosiasi Dosen Muda Indonesia, 2025)
This study investigates the influence of organizational culture and work motivation on employee performance at PT Zurich Insurance in Tangerang. Organizational culture, represented by principles such as honesty, excellence, respect, and enthusiasm, plays a significant role in shaping employee behavior and creating a conducive work environment. Similarly, work motivation, driven by factors such as recognition, job security, and opportunities for self-development, is identified as a critical factor in improving employee engagement and productivity. The research employs a quantitative method with an associative approach, involving a population of 73 employees. Data collection utilized a survey method with structured questionnaires, and the results were analyzed using multiple linear regression. The findings reveal that both organizational culture and work motivation have a significant positive effect on employee performance, both individually and simultaneously. Organizational culture contributes to fostering teamwork, attention to detail, and results orientation, while work motivation drives employees to achieve higher performance levels. When combined, these factors exhibit a synergistic effect, emphasizing their interconnectedness in shaping overall employee performance. This study underscores the importance of continuously enhancing organizational culture and designing motivational policies that address employee needs while aligning with company objectives. PT Zurich Insurance is advised to focus on training, performance recognition, and work-life balance to sustain employee productivity and well-being. The research contributes to the literature on human resource management by emphasizing the critical role of tailored strategies in achieving organizational success in a competitive business environment.